Associations between lifetime PTSD symptoms and current substance use disorders using a five-factor model of PTSD. (January 2015) - Trautmann, S.; Schönfeld, S.; Behrendt, S.; Schäfer, J.; Höfler, M.; Zimmermann, P.; Wittchen, H.-U.
Highlights: We analyzed associations between lifetime PTSD symptoms, current alcohol use disorders (AUD) and nicotine dependence (ND). Associations between PTSD symptoms, AUD and ND were reduced when considering comorbidity. The occurrence of lifetime numbing symptoms was associated with current ND beyond other symptom clusters and comorbid disorders. The number of re-experiencing symptoms was associated with current ND beyond other symptom clusters and comorbid disorders. Dysphoric and anxious arousal PTSD symptoms were differentially related to the risk for current AUD. Abstract: This paper aimed to extend the existing knowledge on the association between PTSD symptoms, alcohol use disorders (AUD) and nicotine dependence (ND) by distinguishing between anxious and dysphoric arousal PTSD symptoms and by considering the putative contribution of additional comorbidity. Data stem from a cross-sectional study in a stratified, representative sample of 1483 recently deployed soldiers using standardized diagnostic interviews. All lifetime PTSD symptom clusters (occurrence of any symptom and number of symptoms) were associated with current AUD and ND in crude models except that anxious arousal was not related to AUD. Associations were reduced in magnitude when controlling for comorbidity. Current ND was related to the occurrence of any emotional numbing and to the number of re-experiencing symptoms above the contribution of other symptom clusters and comorbidity. In conclusion, associations between PTSD symptoms, AUD and ND may be partially attributable to additional comorbidity. Findings also yield further evidence for a role of emotional numbing and re-experiencing symptoms in the comorbidity between PTSD and ND and for a distinction between dysphoric and anxious arousal PTSD symptoms.